Analisa Proyek pada Usaha Bisnis Sociopreneurship Produk Glowish - Destiana Safitri; Putri Tazkia; Xena Amanda; Yuliana Shintia; Tata Fransiska Putri; Sevilla Nadia Amada; Renny Christiarini (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
This article was created to research one of the business ideas to be developed, namely Glowish Products which is a social-based business idea made from recycled materials derived from fruit peels. This research focuses on a business idea that is made into a project aimed at achieving the goals desired by the business. The project that is carried out is carefully planned until it forms the deliverables expected by the business. The research method used is descriptive method. The results of the analysis obtained consist of project integration, scope, time, and quality of the business being run. This article also uses the critical path method for scheduling the project to be carried out with the need for a good controlling system.